METABOLIC TREATMENT IN COMPLEX THERAPY OF INFANTS WITH PERINATAL LESIONS OF CENTRAL NERVOUS SYSTEM - L.N. Melnik; M.N. Fedorova (Вопросы современной педиатрии)
(Voprosy sovremennoi pediatrii — Current Pediatrics. 2010;9(5):136-137)